2019
DOI: 10.3892/ol.2019.11008
|View full text |Cite|
|
Sign up to set email alerts
|

A combination of inhibitors of glycolysis, glutaminolysis and de�novo fatty acid synthesis decrease the expression of chemokines in human colon cancer cells

Abstract: Lonidamine, 6-Diazo-5-oxo-L-norleucine (DON) and orlistat are well known inhibitors of glycolysis, glutaminolysis and of de novo fatty acid synthesis, respectively. Although their antitumor effects have been explored in detail, the potential inhibition of the malignant metabolic phenotype and its influence on the expression of chemokines and growth factors involved in colon cancer, have not been previously reported to the best of our knowledge. In the present study, dose-response curves with orlistat, lonidami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Confirming our previous findings 16 , we observed strong growth inhibitory effects in vitro which were associated with G 0 /G 1 arrest of cell cycle and increased apoptosis. As far as we know, there are no publications testing cell cycle or cell death with a combination of inhibitors of these pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Confirming our previous findings 16 , we observed strong growth inhibitory effects in vitro which were associated with G 0 /G 1 arrest of cell cycle and increased apoptosis. As far as we know, there are no publications testing cell cycle or cell death with a combination of inhibitors of these pathways.…”
Section: Discussionsupporting
confidence: 92%
“…5 × 10 4 SW480 cells/well were seeded in 6-well plates (Costar), with 2 mL of complete medium. After 24 h of pre-incubation, cells were treated during 72 h with orlistat, lonidamine, or DON at synergistic concentrations, as stated before 16 , and with the maximum circulating concentrations of GH, insulin, or indomethacin, reported in healthy subjects [45][46][47] . The concentrations are found on Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Orlistat is a tetrahydrolipstatin ( Figure 6) which is an FDA approved gastric and pancreatic lipase inhibitor that works in the intestine by hindering fat absorption by up to 30%, It is used mainly as a weight loss medication in obese patients [158]. Several studies investigated the effect of Orlistat as an antitumorigenic drug in various cancers such as T-cell Leukemia [158], melanoma [159], colorectal cancer [160,161], prostate cancer [162], hepatoma [163], breast cancer, and pancreatic cancer [164]. Orlistat suppresses tumor growth by inhibiting Fatty Acid Synthase (FASN), an anabolic multifunctional enzyme responsible for endogenous fatty acid synthesis from precursors acetyl-CoA and malonyl-CoA to make the 16 carbon polyunsaturated fatty acid palmitate [165,166].…”
Section: Orlistatmentioning
confidence: 99%
“…Furthermore, the study showed that the combination of both Orlistat and Paclitaxel had a strong synergistic effect on growth inhibition and cell apoptosis in Hep3B cells [163]. Additionally, when Orlistat was combined with Lonidamine and 6-Diazo-5-oxo-L-norleucine (DON) for treatment of SW480 colon cancer cells, they exhibited a synergistic cytotoxic effect with downregulation of their protein targets Hexokinase-2 (HK2), Glutaminase-1 (GLS-1), and Fatty Acid Synthase (FASN), respectively [160]. Finally, a study by Saleh et al indicated that Orlistat exerted a cytotoxic effect and induced apoptosis in human breast cancer (MCF-7) and human pancreatic cancer (PANC-1) cell lines [164].…”
Section: Orlistatmentioning
confidence: 99%
“…For the top colon cancer MEGs, the consistent tumor suppressor genes included MAP2K4, MAPK10, RUNX3, WNK2 (the four genes were identified by the TSGene 2.0 database), BECN1 [ 27 ], FASN [ 28 ], NAT1 [ 29 ], and NR3C2 [ 30 ]. For monotonically increasing genes, the consistent ones include CCKBR, BMP4 [ 31 , 32 ], and SLC29A1 [ 33 ] which were determined to be oncogenes by previous studies.…”
Section: Resultsmentioning
confidence: 99%